REVIEW ARTIKEL: IDENTIFIKASI FITOKIMIA, POTENSI AKTIVITAS ANTIOKSIDAN DAN TOKSISITAS DAUN BALAKACIDA (Chromolaena odorata L.) - Marsella, Virna Rindra; Saleh, Chairul (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Balakacida is a plant that grows in open areas and thrives in plantations, so this plant is often referred to as a weed. This plant is often used as a live pharmaceutical plant to cure several diseases. Various studies on the phytochemical content of Balakacida plants have been conducted. Phytochemical identification of Balakacida plants shows that Balakacida plants contain phytochemical aglycones, flavonoids, terpenoids, essential oils, alkaloids, saponins, tannins and steroids. Literature studies show that Balakacida leaves have toxicity activity shown in the LC50 value. The LC50 values obtained in the crude extract, n-hexane fraction, ethyl acetate are 2.88 ppm, 8.12 ppm and 6.86 ppm respectively. It is known that Balakacida plants have high antioxidant content, this is influenced by its high flavonoid levels. In Balakacida leaf extract, having an IC50 value of 23.4 µg/mL. So that researchers can conclude that Balakacida leaf extract has phytochemical content of aglycone groups, flavonoids, terpenoids, essential oils, alkaloids, saponins, tannins and steroids, with very strong toxicity and antioxidant activity. Keywords: Antioxidant, Balakacida, phytochemical identification, toxicity